Mapping the CLEC12A expression on myeloid progenitors in normal bone marrow; implications for understanding CLEC12A‐related cancer stem cell biology. Issue 4 (7th February 2018) - Bill, Marie; B. van Kooten Niekerk, Peter; S. Woll, Petter; Laine Herborg, Laura; Stidsholt Roug, Anne; Hokland, Peter; Nederby, Line
Abstract: The C‐type lectin domain family 12, member A (CLEC12A) receptor has emerged as a leukaemia‐associated and cancer stem cell marker in myeloid malignancies. However, a detailed delineation of its expression in normal haematopoiesis is lacking. Here, we have characterized the expression pattern of CLEC12A on the earliest stem‐ and myeloid progenitor subsets in normal bone marrow. We demonstrate distinct CLEC12A expression in the classically defined myeloid progenitors, where on average 39.1% (95% CI [32.5;45.7]) of the common myeloid progenitors (CMPs) expressed CLEC12A, while for granulocyte‐macrophage progenitors and megakaryocyte‐erythroid progenitors (MEPs), the average percentages were 81.0% (95% CI [76.0;85.9]) and 11.9% (95% CI [9.3;14.6]), respectively. In line with the reduced CLEC12A expression on MEPs, functional assessment of purified CLEC12A +/− CMPs and MEPs in the colony‐forming unit assay demonstrated CLEC12A + subsets to favour non‐erythroid colony growth. In conclusion, we provide evidence that the earliest CLEC12A + cell in the haematopoietic tree is the classically defined CMP. Furthermore, we show that CLEC12A‐expressing CMPs and MEPs are functionally different than their negative counterparts. Importantly, these data can help determine which cells will be spared during CLEC12A‐targeted therapy, and we propose CLEC12A to be included in future studies of myeloid cancer stem cell biology.